Agrotourism Tourism Village Development Model Ngebret Hamlet, Morowudi Village, Cerme District, Gresik Regency - Kartika, Chandra; Indrawati, Mei; Sarie, Rena Febrita; Sri Lestari, Veronika Nugraheni (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: Development Model of Agrotourism Tourism Village, Ngebret Hamlet, Morowudi Village, Cerme District, Gresik Regency. This further research aims to test and analyze the Development Model of Agrotourism Tourism Village, Ngebret Hamlet, Morowudi Village, Cerme District, Gresik Regency The sample in the study was 15 correspondents related to agrotourism tourism villages. Design/methodology/approach: The sampling method used in this study is to take it to the concerned corespodent. The data collection method was carried out by distributing interviews to correspondents related to agrotourism tourism villages, namely respondents in Ngebret Hamlet, Morowudi Village, Cerme District, Gresik Regency. The data analysis technique is SWOT strategy analysis. Findings: From this advanced research activity, it resulted in the contribution of the development of agrotourism tourism villages to the improvement of the regional economy in Morowudi Ngebret Village, Cerme District, Gresik Regency through the development of agrotourism tourism villages that can increase profitability and business development well and can improve village economic development in Ngebret Hamlet, Morowudi Village, Cerme District, Gresik Regency. Paper type: Research Paper.